TANTANGAN GURU DALAM MENGAJAR DENGAN SISTEM WORK FROM HOME PADA MASA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH - Hasan Hasan (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2021)
The purpose of this study wa to determine the challenge faced by teachers in implementin pedagogic competencies during the teaching process with a work from home system. This  research is located  at the Madrasah  Ibtidaiyah  Lemo Tua, Kuajang Village, Binuang District,Polewali Mandar Regency,West Sulawesi Province.The research subjects were 6 class teachers. This research is an exploratory case study using a qualitative research approach with data analysis techniques using  triangulation. The  results of the study found that the challenges  faced by teachers were 1) teachers had  difficulties in achieving  learning  targets  according  to the  curriculum, 2) teachers had difficulties in implementing online learning using technology media, 3) teachershad difficulties in assessing student learning outcomes in accordance with validation instruments and reliable data. These challenges cause teachers to be unable to maximize their pedagogical competence  in teaching with a work from home system. Researchers offer ideas to answer these challenges, namely,1) the need for  simplification of learning  and assessment targets, 2) the  need for provision of digital literacy knowledge and the use of technology for teachers, students and parents,3) the need for smartphone subsidies for teachers and  students during the pandemic.